Autoarquivamento e representação de assunto: estudo analítico de teses e dissertações do Repositório Institucional da UFSCar - Freitas, Marina Penteado de (2019)
There is a lack of research in the Information Science literature on self-archiving in institutional repositories, regarding the quality of representation of the documentary information and, consequently, the information retrieval capabilities. Investigations on the indexing practices of scientific production using self-archiving procedures are relevant on order to contribute to the improvement of quality both of information representation and of information retrieval by subject in institutional repositories. The research focus of this dissertation is on the lack of empirical investigation on the consequences of information retrieval in open access institutional repositories. Therefore, the aim is to investigate the self-archiving effects on the consistency in indexing by subject in institutional repositories focusing on the theses and dissertation collection. The empirical investigation concentrated on analyzing the results of unmediated self-archiving by authors/researchers compared to the same process executed by a librarian specialized in self-archiving. The evaluation centered on the dissertations and theses of the Science, Technology, and Society Postgraduate Programme available in the Institutional Repository of the Federal University of Sao Carlos (UFSCar). The aim is to contribute from a theoretical-methodological perspective to harmonize self-archiving practices and the consistency in indexing scientific production of the Brazilian institutional repositories. The secondary objectives are the following: a) contextualize the institutional repositories from the Information Science perspective emphasizing the modern practices of documentary information representation in a digital context; b) characterize self-archiving practices in both national and international institutional repositories; c) investigate the indexing consistency of theses and dissertations in the RI/UFSCar applying the intrinsic qualitative evaluation method. The investigation is exploratory and descriptive, applying the bibliographic research method to perform a qualitative analysis. The results show a similarity between the indexes evaluated, but the user’s indexation took more time and was less precise than the expert librarian’s indexation. A possible solution to deal with the lack of terms precision is to provide documentary languages to users/researchers as references for terms assignment, subject metadata validation by librarians, and indexing policies elaboration to improve representation and retrieval by subjects in institutional repositories.